The Food4toddlers study - study protocol for a web-based intervention to promote healthy diets for toddlers: a randomized controlled trial - Margrethe Røed; Elisabet R. Hillesund; Frøydis N. Vik; Wendy Van Lippevelde; Nina Cecilie Øverby (BMC, 2019)
Abstract Background Eating habits are established during childhood and track into adolescence and later in life. Given that these habits have a large public health impact and influence the increasing rates of childhood obesity worldwide, there is a need for effective, evidence-based prevention trials promoting healthy eating habits in the first 2 years of life. The aim of this study was to develop and evaluate the effect of an eHealth intervention called Food4toddlers, aiming to promote healthy dietary habits in toddlers by targeting parents' awareness of their child's food environment (i.e., how food is provided or presented) and eating environment (e.g., feeding practices and social interaction). This paper describes the rationale, development, and evaluation design of this project. Methods/design We developed a 6-month eHealth intervention, with the extensive user involvement of health care nurses and parents of toddlers. This intervention is in line with the social cognitive theory, targeting the interwoven relationship between the person, behavior, and environment, with an emphasis on environmental factors. The intervention website includes recipes, information, activities, and collaboration opportunities. The Food4toddlers website can be used as a mobile application. To evaluate the intervention, a two-armed pre-post-follow-up randomized controlled trial is presently being conducted in Norway. Parents of toddlers (n = 404) were recruited via social media (Facebook) and 298 provided baseline data of their toddlers at age 12 months. After baseline measurements, participants were randomly allocated to an intervention group or control group. Primary outcomes are the child's diet quality and food variety. All participants will be followed up at age 18 months, 2 years, and 4 years. Discussion The results of this trial will provide evidence to increase knowledge about the effectiveness of an eHealth intervention targeting parents and their toddler's dietary habits. Trial registration ISRCTN92980420. Registered 13 September 2017. Retrospectively registered.